2017
DOI: 10.1016/j.jvs.2017.06.068
|View full text |Cite
|
Sign up to set email alerts
|

Association between arterial stiffness and peripheral artery disease as measured by radial artery tonometry

Abstract: Objective Arterial stiffness and peripheral artery disease (PAD) are both associated with an elevated risk of major adverse cardiac events (MACE); however, the association between arterial stiffness and PAD is less well characterized. The goal of the present study was to examine the association between parameters of radial artery tonometry, a non-invasive measure of arterial stiffness, and PAD. Methods We conducted a cross-sectional study of 134 vascular surgery outpatients (controls=33, PAD=101) using arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 45 publications
0
35
0
1
Order By: Relevance
“…The ratio is calculated from the peripherally reflected pulse wave, the amplitude and speed of which are dependent upon arterial stiffness; thus, the AIx reflects systemic arterial stiffness . Previous studies have reported that the AIx derived from PAT was not only reproducible but also closely correlated with the aortic AIx or radial AIx, and central and peripheral AI are also highly correlated . The AIx has been used to evaluate peripheral vascular lesions in many studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ratio is calculated from the peripherally reflected pulse wave, the amplitude and speed of which are dependent upon arterial stiffness; thus, the AIx reflects systemic arterial stiffness . Previous studies have reported that the AIx derived from PAT was not only reproducible but also closely correlated with the aortic AIx or radial AIx, and central and peripheral AI are also highly correlated . The AIx has been used to evaluate peripheral vascular lesions in many studies.…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al evaluated the relationship between DR and peripheral AIx in 95 patients and found that patients with more severe DR had greater peripheral vascular stiffness . Zahner et al conducted a study of 101 patients with peripheral artery disease (PAD) and found that patients with PAD had a significantly higher central AIx and peripheral AIx than the control group after adjusting for several atherosclerotic risk factors . Several noninvasive techniques have been studied to evaluate the grade of intrarenal arteriosclerosis, such as the renal Doppler resistive index (RI); what has been found is that the higher the RI is, the more severe the atherosclerosis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Вместе с тем, проблема тромботических ок клюзий и стенозов зоны артериальной реконструкции остается актуальной и существенно ограничивает широкое внедрение хирургических методов. Очень важную роль в развитии этих осложнений играют факторы риска, ассоциированные с атеросклерозом, которые хорошо известны и освещены во многих работах [7][8][9][10][11][12][13][14]. Неудовлетворительные отдаленные результаты лечения связывают, прежде всего, с высокой степенью активности атеросклеротического процесса, особенно у больных молодого возраста.…”
Section: Introductionunclassified